2006
DOI: 10.1111/j.1471-0528.2006.01038.x
|View full text |Cite
|
Sign up to set email alerts
|

Linear association between maternal pre‐pregnancy body mass index and risk of caesarean section in term deliveries

Abstract: Objective Maternal obesity is a well-known risk factor for caesarean delivery. The aim of this study is to determine whether all the spectrum of pre-pregnancy maternal corpulence (body mass index [BMI]) is associated with the risk of caesarean delivery.Design Observational study over 4.5 years .Setting Groupe Hospitalier Sud-Réunion's maternity (island of La Réunion, French overseas department, Indian Ocean).Population All consecutive singleton live births having delivered at the maternity.Methods Data have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
89
1
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(109 citation statements)
references
References 16 publications
13
89
1
6
Order By: Relevance
“…Obesity in the present study was associated with a higher rate of CS (42.9%). Similar findings were reported by others [27,28] and a linear relationship between BMI and cesarean delivery has been reported [29].…”
Section: Discussionsupporting
confidence: 79%
“…Obesity in the present study was associated with a higher rate of CS (42.9%). Similar findings were reported by others [27,28] and a linear relationship between BMI and cesarean delivery has been reported [29].…”
Section: Discussionsupporting
confidence: 79%
“…It has been shown that even with an uncomplicated pregnancy, there was a need for more oxytocin infusion to induce labor in overweight and obese women than in normal weight (42). Moreover, prepregnancy body mass index (43,44) and increase in its category (45) during pregnancy have been found to be high risk factors for caesarean delivery at term of pregnancy for failure to progress in the labor. However, the molecular mechanisms by which obesity and overweight lead to difficult labor remain unknown so far.…”
Section: Discussionmentioning
confidence: 99%
“…Post-dated pregnancies, induction of labor (IOL) and abnormal labor progression are more common in obese women. The rates of both elective and emergency CS successively increase with maternal BMI (11)(12)(13). Postoperative complications, including postpartum hemorrhage, anesthesiology complications, infections and thromboembolic complications, are also more common in obese women (9,14).…”
Section: Maternal Complications Associated With Obesitymentioning
confidence: 99%